PROGRAM MANAJEMEN PELAYANAN PENDIDIKAN UNTUK MEWUJUDKAN PENDIDIKAN YANG BERKUALITAS - TAMBA, IMELDA (Ensiklopedia Education Review, 2019)
Awareness of the importance of education that can provide hope and better possibilities in the future, has encouraged various efforts and attention of all levels of society towards the movement of the educational world. Education as an effort in order to improve the quality of human life, in essence aims to humanize, mature, and change behavior, and improve quality for the better. In reality education is not a simple effort, but an activity that is dynamic and challenging. Education will always change along with the changing times, every time education is always the focus of attention and not even the target of dissatisfaction because education concerns the interests of all people, not only concerning investment and living conditions in the future, but also concerning conditions and atmosphere current life. That is why education always requires improvement and improvement in line with the increasing need and guidance of people's lives. Keywords: Service Management, Education, Quality.